a Evaluation of Primary Service Readiness in Handling Catastrophic Disease Emergencies in Rural Areas: Evaluation of Primary Service Readiness in Handling Catastrophic Disease Emergencies in Rural Areas - Floriana, Callina (JURNAL KESMAS DAN GIZI (JKG), 2023)
Evaluation of Primary Service Readiness in Handling Catastrophic Disease Emergencies in Rural Areas